Analisis Marfu'atul Asma dalam Film Pendek "Inthiq Rasmiyyatan!" Karya Santri Gontor - St. Lutfiatul Adibati; Zahwa Adinda Nurul Fitri; Anggun Putri Maharani; Aang Saeful Milah (Diwan: Jurnal Bahasa dan Sastra Arab, 2024)
This research analyzes the use of marfu'atul asthma and its i'rob signs in the short film "Inthiq Rasmiyyatan". The method used is qualitative descriptive analysis, with data collected through the listening and note-taking method. Data analysis techniques included data collection, analysis, and drawing research conclusions. The findings of this research revealed 22 instances of marfu'atul asthma in the film "Inthiq Rasmiyyatan", consisting of 1 fa'il data, 0 naibul fa'il data, 6 mubtada' khabar data, 1 kana data, 4 inna wa akhawatuha data, and 7 tawabi 'lil marfu' (consisting of 1 na'at data, 1 taukid data, and 2 athaf data).